Effect of Microwave Treatment in Graphite Anode for Microbial Fuel Cell and Its Application in Biosensor - Abdalameer Lafta, Hamzah; K. H. AL-Mashhadani, Mahmood (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The electrode in the microbial fuel cell has a significant effect on cell performance. The treatment of the electrode is a crucial step to make the electrode surface more habitable for bacteria growth, thus, increases the power production as well as waste treatment. In the current study, two graphite electrodes were treated by a microwave. The first electrode was treated with 100W microwave energy, while the second one was treated with 600W microwave energy. There is a significant enhancement in the surface of the graphite anode after the pretreatment process. The results show an increase in the power density from 10 mW/m2 to 15 mW/m2 with 100w treatment and to 13.47 mW/m2 with 600w treatment. An organic sensor was obtained for the same waste material used, where the sensitivity was weak, ranging from 100 mg/L for organic matter to 150 g /L. The sensor was used once again for each substance with better results. The sensitivity ranged from 25 g/L per liter to 150 g/L, while successful linearity has been gain. Therefore, it can conclude that the microbial fuel cell with dual chamber can be designed for a biosensor with the available and cost-effective material.